Asymptotic Stability of a Delay-Difference Control System of Hopfield Neural Networks via Matrix Inequalities and Applications - RATCHAGIT, Kreangkri (Walailak Journal of Science and Technology (WJST), 2011)
We have established a new sufficient condition for the asymptotic stability of a delay-difference control system of Hopfield neural networks in terms of certain matrix inequalities (based on a discrete analog of the Lyapunov second method). The result has been applied to obtain new stability conditions for some class of delay-difference control system such as delay-difference control system of Hopfield neural networks with multiple delays in terms of certain matrix inequalities.